A Pilot Randomized Clinical Trial of Remote Varenicline Sampling to Promote Treatment Engagement and Smoking Cessation. Issue 6 (29th November 2020) - Carpenter, Matthew J; Gray, Kevin M; Wahlquist, Amy E; Cropsey, Karen; Saladin, Michael E; Froeliger, Brett; Smith, Tracy T; Toll, Benjamin A; Dahne, Jennifer
Abstract: Introduction: Medication sampling is a clinically useful tool to engage smokers in the quitting process. Whether varenicline is suitable for sampling purposes is unclear. The purpose of this study was to examine the feasibility, uptake, and preliminary outcomes of varenicline sampling. Methods: Smokers ( N = 99), both motivated to quit and not, were recruited and randomized to varenicline sampling versus not, with 12 week follow-up. The intervention consisted of mailing one-time samples of varenicline (lasting 2–4 wks), with minimally suggestive guidance on use. Results: Uptake of varenicline was strong, at 2 weeks (54% any use, 66% daily use) and 4 weeks (38%, 46%), with 58% of medication users seeking additional medication. Most users followed conventional titration patterns, self-titrating from 0.5 mg to 2 mg. Relative to control, varenicline sampling increased motivation ( p = 0.006) and confidence to quit ( p = 0.02), and decreased cigarette smoking ( p = 0.02). Smokers receiving varenicline samples were significantly more likely to achieve 50% reduction in cigarettes per day (CPD), both immediately following the sampling exercise (Adjusted Odds Ratio [AOR] = 4.12; 95% CI: 1.39 to 12.17) and at final follow-up (AOR = 4.50; 95% CI: 1.56 to 13.01). Though cessation outcomes were not statistically significant, there was a 1.5 to 3-fold increase in quit attempts and abstinence from varenicline sampling throughout follow-up. These outcomes were comparable among smokers motivated to quit and not. Conclusions: Unguided, user-driven sampling of varenicline sampling is a concrete behavioral exercise that is feasible to do and seems to suggest clinical utility. Sampling is a pragmatic clinical approach to engage more smokers in quitting. Implications: Use of evidence-based pharmacotherapies for smoking cessation is low. Medication sampling is a pragmatic behavioral exercise that allows smokers to experience the benefits of using them, while promoting positive downstream effects towards quitting. While previous studies have shown that nicotine replacement therapy (NRT) sampling is viable and effective, whether this extends to varenicline is unclear. Results from this trial demonstrate that varenicline sampling is feasible, safe, and suggestive of clinically important steps toward quitting, deserving of a larger trial. Clinical Trial Registration: NCT #03742154.